1992
DOI: 10.1111/j.1476-5381.1992.tb14518.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of selective antagonists to dissociate the central cardiovascular and behavioural effects of tachykinins on NK1 and NK2 receptors in the rat

Abstract: 1 The effects of intracerebroventricular (i.c.v.) pretreatment with selective NKI ((±)-CP 96,345), NK2, (MEN 10,207; MEN 10,376)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 38 publications
1
19
1
Order By: Relevance
“…This observation is in agreement with previous studies that reported an enhanced locomotion in the guinea-pig (Brent et al, 1988;Seymour et al, 1991) and in the rat (Jolicoeur et al, 1980;Naranjo & Del Rio, 1984 (Petitet et al, 1992;Geraghty et al, 1993;Maggi et al, 1993b;Pradier et al, 1994) The selective NK2 tachykinin receptor agonist [Lys5, Me-Leu9, Nle1INKA(4-10) did not induce, up to the dose of 20 pg, any behavioural responses in the guinea-pig in our experimental design. The data obtained in this species appeared quite different from those reported at the same doses in mice and rats, in which excessive grooming and washing are seen when given various NK2 receptor agonists [Lys5, MeLeu9, Nle'INKA(4-10), NKA and D-septide (Elliott & Iversen, 1986;Sakurada et al, 1989;Tschope et al, 1992;Culman et al, 1993;Picard et al, 1994;Ravard et al, 1994). Moreover, rotational responses to intranigral infusion of selective NK2 receptor agonists in rats have been described (Elliott et al, 1991).…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…This observation is in agreement with previous studies that reported an enhanced locomotion in the guinea-pig (Brent et al, 1988;Seymour et al, 1991) and in the rat (Jolicoeur et al, 1980;Naranjo & Del Rio, 1984 (Petitet et al, 1992;Geraghty et al, 1993;Maggi et al, 1993b;Pradier et al, 1994) The selective NK2 tachykinin receptor agonist [Lys5, Me-Leu9, Nle1INKA(4-10) did not induce, up to the dose of 20 pg, any behavioural responses in the guinea-pig in our experimental design. The data obtained in this species appeared quite different from those reported at the same doses in mice and rats, in which excessive grooming and washing are seen when given various NK2 receptor agonists [Lys5, MeLeu9, Nle'INKA(4-10), NKA and D-septide (Elliott & Iversen, 1986;Sakurada et al, 1989;Tschope et al, 1992;Culman et al, 1993;Picard et al, 1994;Ravard et al, 1994). Moreover, rotational responses to intranigral infusion of selective NK2 receptor agonists in rats have been described (Elliott et al, 1991).…”
Section: Discussioncontrasting
confidence: 44%
“…SP or related compounds, which possess a high affinity for tachykinin NKI sites, lead to enhanced locomotor activity, awareness, scratching, grooming and face-washing behaviour when injected intracerebroventricularly (i.c.v.) in conscious freely moving rats (Jolicoeur et al, 1980;Elliott & Iversen, 1986;Itoi et al, 1992;Tschope et al, 1992). In mice, the NK1 receptor agonists have been shown to increase locomotor activity (Naranjo & Del Rio, 1984;Elliott et al, 1991) and to induce scratching and grooming (Ravard et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with our previous findings (Culman et al, 1993) (Takano et al, 1990;Itoi et al, 1992;Tschope et al, 1992;Culman et al, 1993). It has been suggested that, at low concentrations, SP, NKA and NKB, are selective for particular tachykinin receptor binding sites (Helke et al, 1990).…”
Section: Introductionsupporting
confidence: 93%
“…In the case of SP, NKA and NPy, these effects were ascribed to sympathetic nervous system stimulation (Unger et al, 1981;1985;Takano et al, 1990;Hagio et al, 1991). A behavioural arousal reaction including increased locomotion and intense scratching and grooming behaviour accompanies these haemodynamic effects Tschope et al, 1992;Picard et al, 1994;Prat et al, 1994). Surprisingly, the order of potency for these natural tachykinins on the cardiovascular system after central administration is NPK > NPy > SP > NKA > NKB (Couture et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…NPy leads one to suggest that receptor sites must be localized in the circumventricular organs or in adjacent periventricular structures. A peripheral site of action is also unlikely since these peptides are vasodilators and reduce blood pressure after systemic administration (Couture et al, 1989; Decarie & Couture, 1992). The cardiovascular changes elicited by i.c.v.…”
Section: Discussionmentioning
confidence: 99%